Analisis Struktur Dan Harmoni Lagu Godang Do Nian Karya Wira Purba Dan Anis Gea - Banjarnahor, Fitria; Simanjuntak, Hendrik L.; simangunsong, Emmi (Innovative: Journal Of Social Science Research, 2024)
This study discusses the analysis of the structure and harmony of the song Godang Do Nian by Wira Purba and Anis Gea. The song Godang Do Nian is a Batak Toba song which is classified as a popular regional song created and published through the social media YouTube in 2021. This song is sung as a duet by Onsimson and Anis Gea using guitar, piano and string ensemble instruments with andante tempo. The theoretical basis used in this study is the Karl-Edmund Prier SJ theory to obtain the structure and harmony of the song. The author then uses a qualitative descriptive research method. The results of the author's research are a transcription of the song Godang Do Nian by Wira Purba and Anis Gea, then an analysis through the structure where the song Godang Do Nian is a two-part song form with periods A, A, B, A', B' and B' and the harmony of the song Godang Do Nian which uses the E♭ Major scale which is built with basic chords from the notes in the E♭ Major scale (E♭, Fm, Gm, A♭, B♭, Cm, and Ddim). Overall, although there are chord variations in the song, the harmony remains rooted in E♭ Major. Then before the ending, the song undergoes modulation from the tonality of E♭ Major to C Major.